Survival Benefits Following Liver Transplantation: A Matched-pair Analysis in Pediatric Patients With Cystic Fibrosis. Issue 3 (September 2021) - Flemming, Gunter; Baumann, Ulrich; Richter, Nicolas; Vondran, Florian; Tümmler, Burkhard; Dittrich, Anna-Maria; Müller, Carsten; Vogel, Mandy; Pfister, Eva-Doreen
ABSTRACT: Objectives: Cystic fibrosis-related liver disease (CFLD) with consecutive cirrhosis is the third most common cause of death in CF patients. The aim of this study was to identify the potential long-term benefits of liver transplantation (LTx) in a match-control comparison. Methods: Retrospective single-center data analysis of all pediatric LTx for CFLD between 1998 and 2014. A control group was selected from the local CF patient registry. Data were collected from case report forms and included clinical and laboratory data, lung function tests, the indication for LTx, and details of surgical procedures. Results: At our institution, 23 patients with severe CFLD median age 13.8 years (range 8.7–17.4; 16 boys) underwent LTx between 1998 and 2014. In all patients, normalization of hepatic CF manifestations were achieved after LTx. But obviously there was no significant positive influence on nutritional status. Signs of posttransplant liver steatosis were documented by ultrasound in 17 patients. Liver biopsies after LTx were performed in 19 patients, in 42% (n = 8) of these biopsies a fatty degeneration was observed. Five patients died after LTx, none because of primary hepatic dysfunction (1 because of posttransplant proliferative disorder, 4 because of infection). Analysis of matched control pairs revealed that liver function, anthropometry, pulmonary function, and life expectancy of CFLD patients with LTx are comparable with matched CF peers without CFLD. Conclusions: Isolated LTx normalizes the hepatic manifestation of CF disease. LTx enables children and adolescents with severe CFLD to have a comparable prognosis in terms of growth, life expectancy, and lung function as CF patients without advanced liver involvement. Our data clarifies the long-term perspectives of affected patients. Abstract : Supplemental Digital Content is available in the text